Incorporation of fly ashes from the incineration of MSW in cement mortars - Taborda, P. (2002)
The management of municipal solid wastes (MSW) is currently a problem that requires to be jointly addressed in different ways, to ensure a sustainable development. In order to optimise the management of MSW it is necessary to adopt simultaneously various solutions. Accordingly, incineration has been considered as the main solution for MSW final treatment, due to its efficiency in the reduction of the weight and volume. However, prior to incineration, all the recycable components ought to be separated. After, it is of utmost importance to find solutions for the final incineration waste; in such a manner that landfill disposal is minimised. This reasoning was the basis for the present work, which aims at finding a valorisation of the fly ashes resulting from the Energy Recovery Plant - Lipor II, by incorporating them in cement mortars, to evaluate their possible utilisation in building construction. The incorporation of the ashes took place in two ways, replacing either a certain percentage of cement or a certain percentage of sand. The specimens produced were submitted to flexure and compression tests as well as leaching tests. The results obtained were very encouraging, because the level of danger of the studied waste is much smaller than usually mentioned in literature. Leaching tests showed that was only released aluminium, and in smaller amounts that in the leachate of the control specimen. The incorporation of the ashes leads to a decrease in mechanical resistances, but this can be refuted using cement from a superior class. In conclusion, the fly ashes can be used in the production of cement mortars for the building construction. This substitution can contribute to significant savings in natural raw materilas, helping the preservation of natural resources. Furthermore, decreasing the need for land filling.